A novel S-scheme heterojunction based on 0D/3D CeO2/Bi2O2CO3 for the photocatalytic degradation of organic pollutants. (3rd August 2022) - Wang, Chuantao; Dang, Yuechen; Pang, Xiangxiang; Zhang, Le; Bian, Yujie; Duan, Wen; Yang, Chunming; Zhen, Yanzhong; Fu, Feng
Abstract : Electron directional transfer driven by a built-in electric field and band bending formed a step-scheme heterostructure. Abstract : A distinct S-scheme heterojunction 0D/3D CeO2 /Bi2 O2 CO3 photocatalyst was successfully synthesized by a hydrothermal method for the photocatalytic degradation of methylene blue (MB), tetracycline (TC) and aureomycin (AM). Compared with bare Bi2 O2 CO3 and CeO2, CeO2 /Bi2 O2 CO3 possesses admirable photodegradation capacity. Additionally, the influence of the molar ratio of CeO2 in the compounds was also discussed, and the optimal molar ratio was identified as 15% ( n Ce / n Bi ), for which the photodegradation of MB reaches 98% in 120 min with light irradiation. Favorable retrogradation effects were achieved in the photodegradation of TC and AM. Furthermore, UV–vis diffuse reflectance spectroscopy revealed that the absorption range of solar illumination was successfully expanded to the visible light range for the CeO2 /Bi2 O2 CO3 composites (with a molar ratio of 15%). Besides, based on photoelectrochemical detection, active species capture experiment and density functional theory (DFT), the constructed catalyst conforms to a step-scheme (S-scheme) heterojunction charge transfer mechanism. The satisfactory degradation activity and the outstanding solar light response performance benefit from the driving force in the space separation of photogenerated carriers, optimized energy band structure and high-quality redox capacity. It is speculated that the novel CeO2 /Bi2 O2 CO3 composite would have broad application prospects in the degradation of organic contaminants.